O jogo das escolhas eleitorais: entrada estratégica dos partidos políticos nas eleições majoritárias estaduais sob a regra da verticalização das coligações eleitorais - Carvalho, Valter Rodrigues de (2012)
By transforming the constest in the arena of a negotiation game with prizes and contextual in a game of rationality and equilibrium invariant dominant, how did the TSE, raised the costs of coordinating national electoral bases. This explains in large measure because the vertical coordinate effectively failed the electoral strategies of parties. Contrary to this, there was a shift in the strategies of regional imputs of parties in elections governed by the rule. The clearest example of this occurred in 2006 when the parties withdrew almost entirely from the national arena and chose to maximize their choices in elections majoritarian state. Thus, the existence of a national market for inputs, represented by the presidential elections, it ceases to be a strong incentive for parties collectively rationalize their choices, maximizing gains and minimizing losses and thus coordinate their strategies for competing in congressional districts. This is because the costs for the parties to negotiate agreements nationwide reciprocal withdrawals, avoiding double entries in balance, are high so that even the parties that compete in the presidential arena have difficulties to face them. Thus, contrary to the supposed TSE, more efficient coordination of state electoral strategies in the arenas was observed in the 1998 election then electoral dynamic was characterized, because there was no rule of vertical integration, for a game of negotiation in which dominant unbalanced the parties were able to conduct extensive presidential coalitions, allowing support to competitors in the national arena while they could rationalize their choices in context